2008
DOI: 10.3347/kjp.2008.46.3.139
|View full text |Cite
|
Sign up to set email alerts
|

Toxocariasis and Ingestion of Raw Cow Liver in Patients with Eosinophilia

Abstract: Ingestion of raw animal liver has been suggested as a possible mode of infection of human toxocariasis. We evaluated the relationship between toxocariasis and the ingestion of raw meat in patients with eosinophilia of unknown etiology. The study population consisted of 120 patients presenting with peripheral blood eosinophilia (> 500 cells/ l or > 10% of the white blood cell count). They were divided into 2 groups: 104 seropositive patients based on a Toxocara excretory-secretory IgG ELISA and 16 seronegative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
51
2
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 23 publications
4
51
2
2
Order By: Relevance
“…In South Korea, it was observed that patients presenting eosinophilia had a recent history of consuming raw cow liver [32,36] . In our study, despite the absence of an association between this habit and positive ELISA for Toxocara spp., 45.0% of the subjects reported eating undercooked or raw bovine meat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In South Korea, it was observed that patients presenting eosinophilia had a recent history of consuming raw cow liver [32,36] . In our study, despite the absence of an association between this habit and positive ELISA for Toxocara spp., 45.0% of the subjects reported eating undercooked or raw bovine meat.…”
Section: Discussionmentioning
confidence: 99%
“…However, having a pet was not considered a risk/protective factor for toxocariasis. Keeping a dog in a household has been recognised as a risk factor in some [31,32] but not all surveys [21,33] . The influence of cat ownership on a positive ELISA test has been less studied.…”
Section: Discussionmentioning
confidence: 99%
“…Outras maneiras de transmissão ocorrem por meio do consumo de carne crua ou mal passada de hospedeiros paratênicos, pois estes tem a larva infectante alojada nos tecidos, ou ainda por meio da transmissão congênita. As crianças são mais susceptíveis pelo contato com o solo contaminado por ovos embrionados do parasito enquanto brincam, pelos hábitos geofágicos, e pela imaturidade do sistema imunológico (6)(7)(8) . Como os seres humanos são hospedeiros acidentais, o parasito não completa o seu ciclo, as larvas então, migram por diversos órgãos causando processos patológicos como hipereosinofília crônica, que podem ser acompanhadas por leucocitose e lesões granulomatosas.…”
Section: Introductionunclassified
“…1 The infection of humans occurs by ingestion of eggs that are present in the soil via foods such as vegetables and by consumption of the meat and/or raw or undercooked viscera of chicken, ducks, or cattle infected with T. canis larvae. [2][3][4] Once ingested, the eggs hatch in the intestinal lumen, and the larvae are then released into the circulatory system and settle in various organs and tissues, including the eye, brain, lungs, liver, and muscles. 5 The host immune response involves both the innate and the adaptive systems.…”
Section: Introductionmentioning
confidence: 99%